C2 in a Box: Determining Its Intrinsic Bond Strength for the X1Σg+ Ground State. Issue 12 (7th January 2016) - Zou, Wenli; Cremer, Dieter
Abstract: The intrinsic bond strength of C2 in its 1 Σg + ground state is determined from its stretching force constant utilizing MR‐CISD+Q(8, 8), MR‐AQCC(8, 8), and single‐determinant coupled cluster calculations with triple and quadruple excitations. By referencing the CC stretching force constant to its local counterparts of ethane, ethylene, and acetylene, an intrinsic bond strength half way between that of a double bond and a triple bond is obtained. Diabatic MR‐CISD+Q results do not change this. Confinement of C2 and suitable reference molecules in a noble gas cage leads to compression, polarization, and charge transfer effects, which are quantified by the local CC stretching force constants and differences of correlated electron densities. These results are in line with two π bonds and a partial σ bond. Bond orders and bond dissociation energies of small hydrocarbons do not support quadruple bonding in C2 . Abstract : The C2 conundrum—a never‐ending story : Multireference‐coupled cluster calculations of free and confined dicarbon, C2, lead to a bond strength order of 2.5 relative to that of ethane according to adiabatic/diabatic calculations and local stretching force constants. Electron density and energy density together with Wiberg and Mayer bond indices, all determined at the multireference level, suggest a bond multiplicity lower than 3 in line with the bond strength order.